Overburden and surface subsidence with slicing paste filling mining in thick coal seams - Zheng, Qiushuang; Wang, Changfeng; Pang, Lifu (Frontiers in Earth Science, 2023)
To overcome the difficulties of overburden failure and surface subsidence induced by the slicing mining of extra-thick coal seams, slicing filler paste is typically utilized. In this paper, a continuous curved beam mechanical model of paste filling mining was established by theoretical analysis against the background of the 3305 working face of Yangcheng Coal Mine, the main controlling factors of surface subsidence were analyzed using an orthogonal experiment method (OEM) and an analytic network process (ANP) coupled comprehensive assignment, and the vertical displacement distribution of the overlying rock under different filling intensity was simulated using numerical simulation software. The following main findings were obtained. First, the elastic modulus of the backfill is the primary regulating factor, as demonstrated by the results. Second, the greater the filling body’s elastic modulus, the more efficiently it carries the overburden load and minimizes the maximum surface subsidence. Third, the distance from the open-cut mine likewise reflects the degree of surface subsidence, with the amount of subsidence increasing as the distance from the mine increases.